Training and teaching work in public universities: Characterization and impacts - Sousa, Artemizia Francisca de; Luz, Matheus Osvaldo da Silva (Seven Editora, 2024)
Nowadays both society and the government demand more and more productivity from higher education teachers, generating excessive fatigue and, consequently, compromising their physical and mental health. In this sense, it is important to know the current context that professors at public universities face in their professional lives. The objective of this study was to conduct a survey on the training and work of teachers in public universities. The Support Program for Restructuring and Expansion Plans of Federal Universities democratized access to higher education in Brazil, however, there was a greater demand for training and efficient pedagogical practices that facilitated student learning and not only reproduced content, as in traditional education that still persists today. It is also observed that professors have exhausting routines and debauched salaries, along with an enormous demand for productivity, then developing teaching, research and extension activities, in addition to sometimes participating in commissions and administrative positions. Therefore, it is necessary and urgent to understand the real situation of training and the work of teachers in federal institutions, in order to support more assertive decision-making regarding higher education, so that they can count on qualified and satisfied workers, in which they promote a liberating education and contribute to the development of the country. DOI:https://doi.org/10.56238/sevened2024.009-021